What does peer-to-peer lending evidence say about the risk-taking channel of monetary policy? - Yiping Huang; Xiang Li; Chu Wang (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2019)
This paper uses loan application-level data from a Chinese peer-to-peer lending platform to study the risk-taking channel of monetary policy. By employing a direct ex-ante measure of risk-taking and estimating the simultaneous equations of loan approval and loan amount, we are the first to provide quantitative evidence of the impact of monetary policy on the risk-taking of nonbank financial institution. We find that the search-for-yield is the main workhorse of the risk-taking effect, while we do not observe consistent findings of risk-shifting from the liquidity change. Monetary policy easing is associated with a higher probability of granting loans to risky borrowers and a greater riskiness of credit allocation, but these changes do not necessarily relate to a larger loan amount on average.
urn:nbn:de:gbv:3:2-108242
Keywords: E52; G23; 330; monetary policy; risk-taking; non-bank financial institution; search-for-yield; risk-shifting